Hydrodynamic Calculation and Analysis of a Complex-Shaped ROV Moving near the Wall Based on CFDs - Mengjie Jiang; Chaohe Chen; Zhijia Suo; Yingkai Dong (Journal of Marine Science and Engineering, 2025)
Remotely operated vehicles (ROVs) face challenges in maneuvering and rapidly detecting and repairing large offshore platforms. The accurate research on the hydrodynamics of the ROV, which moves close to the wall, is of great significance for its maneuverability. This study uses computational fluid dynamics (CFDs) to analyze the hydrodynamic characteristics of an ROV when it is moving near the wall, considering factors such as structural asymmetry, speed, and distance from the wall. This study applies multiple linear regression to extract relevant hydrodynamic coefficients and develops a mathematical model that simulates the impact of these factors on ROV performance. The results indicate that the wall’s influence on hydrodynamic forces is significant. Total resistance increases as the ROV moves closer to the wall, and the effect becomes more pronounced at higher speeds. Pressure differential resistance is the dominant factor affecting ROV performance, while viscous resistance remains low and is mostly unaffected by wall proximity. These findings provide valuable insights into calculating hydrodynamic coefficients and modeling the dynamics of ROVs with complex shapes operating near the wall.